2016
DOI: 10.1103/physrevd.94.054035
|View full text |Cite
|
Sign up to set email alerts
|

Production ofY(4260)as a hadronic molecule state ofD¯D

Abstract: We study the Y (4260) production mechanism in e + e − annihilations in the framework of hadronic molecules and investigate the consequence of such a picture in different decay channels. In the hadronic molecule picture the Y (4260) is described as a mixture state composed of a long-ranged DD1(2420) + c.c. molecule state and a compact cc component. We show that the compositeness relation can still provide a reasonable constraint on the wavefunction renormalization parameter due to the dominance of the molecular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 43 publications
4
57
0
Order By: Relevance
“…The recent estimate of Lattice QCD (LQCD) for the leptonic decay width of the Y (4220) is about 40 eV [31] as a feature of the hybrid scenario; the predicted upper limit of the Y (4220) leptonic decay width is about 500 eV if the Y (4220) is a hadronic molecule dominated by DD 1 (2420) [32]; the leptonic decay width is only about 23 eV for the ωχ c0 molecule interpretation [33] where no contributions from the open charm decay channel are included in the analysis.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The recent estimate of Lattice QCD (LQCD) for the leptonic decay width of the Y (4220) is about 40 eV [31] as a feature of the hybrid scenario; the predicted upper limit of the Y (4220) leptonic decay width is about 500 eV if the Y (4220) is a hadronic molecule dominated by DD 1 (2420) [32]; the leptonic decay width is only about 23 eV for the ωχ c0 molecule interpretation [33] where no contributions from the open charm decay channel are included in the analysis.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In a series of recent works it was shown that theDD 1 (2420) + c.c. molecular scenario is favored by the study of cross section lineshapes in those exclusive channels [27][28][29][30][31][32]36]. In particular, the nature of Y(4260) as theDD 1 (2420) + c.c.…”
Section: Nature Of Y(4260) and Production Of Z C (3900) In Y(4260) → mentioning
confidence: 99%
“…As shown in Refs. [30,31] the existence of theDD 1 (2420) + c.c. molecular component can be probed by the cross section lineshapes of exclusive reaction channels in e + e − annihilations.…”
Section: Nature Of Y(4260) and Production Of Z C (3900) In Y(4260) → mentioning
confidence: 99%
“…[15] the angular distribution of the pion in the e + e − c.m. frame with respect to the beam axis is extremely interesting.…”
Section: Resultsmentioning
confidence: 99%
“…Angular distribution of the recoiled pion in the e + e − c.m. frame with respect to the beam axis [15]. The data are from Ref.…”
Section: Resultsmentioning
confidence: 99%